Pneumococcal Conjugate Vaccine Safety in Elderly Adults. (2nd May 2018) - Tseng, Hung Fu; Sy, Lina S; Qian, Lei; Liu, In-Lu A; Mercado, Cheryl; Lewin, Bruno; Tartof, Sara Y; Nelson, Jennifer; Jackson, Lisa A; Daley, Matthew F; Weintraub, Eric; Klein, Nicola P; et al.
Abstract: Background: The 13-valent pneumococcal conjugate vaccine (PCV13) and the 23-valent pneumococcal polysaccharide vaccine (PPSV23) were both recommended to adults aged ≥65 years. The study examines adults ≥65 years for risk of adverse events (AEs) requiring medical attention following vaccination with PCV13 as compared with vaccination with PPSV23, a long-standing vaccine with a satisfactory safety profile. Methods: The cohort study included 6 Vaccine Safety Datalink sites. The exposed person-time included follow-up time of the first PCV13 received by subjects age ≥65 years from January 1 to August 15, 2015. The comparator person-time included follow-up time after the first PPSV23 received by subjects of the same age during Janaury 1 to August 15 of each year of 2011–2015. The prespecified AEs included cardiovascular events, Bell's palsy, Guillain-Barré syndrome, syncope, erythema multiforme, thrombocytopenia, cellulitis and infection, allergic reaction, and anaphylaxis. Inverse probability of treatment weighting–adjusted Poisson regression models was used to estimate the relative risk (RR) of each AE. Results: A total of 313 136 doses of PCV13 and 232 591 doses of PPSV23 were included. The adjusted RRs comparing the incidence of AEs following PCV13 vs PPSV23 were all <1, except for anaphylaxis, which was insignificant with an RR of 1.32 (95% confidence interval, 0.30–5.79). Only 1 patient who received PCV13 and 4 other vaccines concomitantly was confirmed by medical chart review as having experienced anaphylaxis after vaccination. Conclusions: These data do not support an increased rate of adverse events following PCV13 administration in elders compared with PPSV23 and should provide reassurance regarding continued use of PCV13.